2021
DOI: 10.1016/j.heliyon.2021.e06515
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of flavonoids as 2019-nCoV cell entry inhibitor through molecular docking and pharmacological analysis

Abstract: The outbreak of Coronavirus Disease 2019 (COVID-19) has been declared as a Public Health Emergency of International Concern (PHEIC) by the World Health Organization (WHO), which is being rapidly spread by the extremely spreadable and pathogenic 2019 novel coronavirus (2019-nCoV), also known as SARS-CoV-2. Pandemic incidence of COVID-19 has created a severe threat to global public health, necessitating the development of effective drugs or inhibitors or therapeutics agents against SARS-CoV-2. Spike protein (S) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 75 publications
0
25
0
1
Order By: Relevance
“…Recent research teams characterized the interaction site of the S protein of the SARS‐CoV‐2 virus and revealed that flavonoids can bind ACE2, regulate the ACE1 and ACE2 levels, and maintain their basal levels (Bhowmik, Nandi, Prakash, & Kumar, 2021 ; Derosa, Maffioli, D'Angelo, & Di Pierro, 2021 ; El‐Missiry, Fekri, Kesar, & Othman, 2021 ; J. Gao et al, 2021 ; Gour, Manhas, Bag, Gorain, & Nandi, 2021 ; H. Chen & Du, 2020 ; Cherrak, Merzouk, & Mokhtari‐Soulimane, 2020 ; Khan et al, 2021 ; Mendonca & Soliman, 2020 ; Muchtaridi, Fauzi, Ikram, Gazzali, & Wahab, 2020 ; Omotuyi et al, 2021 ; Russo, Moccia, Spagnuolo, Tedesco, & Russo, 2020 ; Tutunchi, Naeini, Ostadrahimi, & Hosseinzadeh‐Attar, 2020 ; J. W. Yu, Wang, & Bao, 2020 ). In addition, disruption of the interaction between ACE2 and the SARS‐CoV‐2 spike protein is the main effect of flavonoids.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Recent research teams characterized the interaction site of the S protein of the SARS‐CoV‐2 virus and revealed that flavonoids can bind ACE2, regulate the ACE1 and ACE2 levels, and maintain their basal levels (Bhowmik, Nandi, Prakash, & Kumar, 2021 ; Derosa, Maffioli, D'Angelo, & Di Pierro, 2021 ; El‐Missiry, Fekri, Kesar, & Othman, 2021 ; J. Gao et al, 2021 ; Gour, Manhas, Bag, Gorain, & Nandi, 2021 ; H. Chen & Du, 2020 ; Cherrak, Merzouk, & Mokhtari‐Soulimane, 2020 ; Khan et al, 2021 ; Mendonca & Soliman, 2020 ; Muchtaridi, Fauzi, Ikram, Gazzali, & Wahab, 2020 ; Omotuyi et al, 2021 ; Russo, Moccia, Spagnuolo, Tedesco, & Russo, 2020 ; Tutunchi, Naeini, Ostadrahimi, & Hosseinzadeh‐Attar, 2020 ; J. W. Yu, Wang, & Bao, 2020 ). In addition, disruption of the interaction between ACE2 and the SARS‐CoV‐2 spike protein is the main effect of flavonoids.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Previous in silico studies and molecular analysis of different CoVs showed the potential antiviral effects of phytochemicals at different stages of viral biogenesis, including binding to ACE2, surface gangliosides, RdRp, viral spike protein, and viral protease in host cells and paved the way for more clinical and experimental studies [ 9 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. Nevertheless, it should be considered that an acceptable antiviral activity in virtual screenings does not necessarily guarantee in vivo antiviral activity, and that is why an overview of flavonoids with antiviral properties in experimental studies is a further step toward the selection of natural antiviral agents.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggests that resveratrol inhibits the entry of virus into Vero cells. In addition to the above studies, several molecular docking and computational studies have described different flavonoids that target SARS-CoV-2 S protein, 3CL pro , PL pro , helicase and RNA polymerase [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. Molecular docking studies have also identified resveratrol, quercetin, and luteolin as phenolic compounds that binds with high affinity to ACE2 receptor [63,64].…”
Section: Flavonoids and Other Natural Phenolic Compounds As Inhibitor...mentioning
confidence: 99%